Innovative Tools for Mechanobiology: Unraveling Outside-In and Inside-Out Mechanotransduction - Mohammed, Danahe; Versaevel, Marie; Bruyère, Céline; Alaimo, Laura; Luciano, Marine; Vercruysse, Eléonore; Procès, Anthony; Gabriele, Sylvain (Frontiers in Bioengineering and Biotechnology, 2019)
Cells and tissues can sense and react to the modifications of the physico-chemical properties of the extracellular environment (ECM) through integrin-based adhesion sites and adapt their physiological response in a process called mechanotransduction. Due to their critical localization at the cell-ECM interface, transmembrane integrins are mediators of bidirectional signaling, playing a key role in “outside-in” and “inside-out” signal transduction. After presenting the basic conceptual fundamentals related to cell mechanobiology, we review the current state-of-the-art technologies that facilitate the understanding of mechanotransduction signaling pathways. Finally, we highlight innovative technological developments that can help to advance our understanding of the mechanisms underlying nuclear mechanotransduction.